Dissection of signaling pathways in fourteen breast cancer cell lines using reverse-phase protein lysate microarray - AKKİPRİK, MUSTAFA (SAGE PUBLICATIONS INC, 2006)
Signal transduction pathways play a crucial role in breast cancer development, progression, and response to different therapies. A major problem in breast cancer therapy is the heterogeneity among different tumor types and cell lines commonly used in preclinical studies. To characterize the signaling pathways of some of the commonly used breast cancer cell lines and dissect the relationship among a number of pathways and some key genetic and molecular events in breast cancer development, such as p53 mutation, ErbB2 expression, and estrogen receptor (ER)/progesterone receptor (PR) status, we performed pathway profiling of 14 breast cancer cell lines by measuring the expression and phosphorylation status of 40 different cell signaling proteins with 53 specific antibodies using a protein lysate array. Cluster analysis of the expression data showed that there was close clustering of phosphatidylinositol 3-kinase, Akt, mammalian target of rapamycin (mTOR), Src, and platelet-derived growth factor receptor beta (PDGFR beta) in all of the cell lines. The most differentially expressed proteins between ER- and PR-positive and ER- and PR-negative breast cells were mTOR, Akt (pThr308), PDGFR beta, PDGFR beta (pTyr751), panSrc, Akt (pSer473), insulin-like growth factor-binding protein 5 (IGFBP5), Src (pTyr418), mTOR (pSer2448), and IGFBP2. Many apoptotic proteins, such as apoptosis-inducing factor, IGFBP3, bad, bax, and cleaved caspase 9, were overexpressed in mutant p53-carrying breast cancer cells. Hexokinase isoenzyme 1, ND2, and c-kit were the most differentially expressed proteins in high and low ErbB2-expressing breast cancer cells. This study demonstrated that ER/PR status, ErbB2 expression, and p53 status are major molecules that impact downstream signaling pathways.
Keywords: protein lysate array; breast cancer; pathway; ER; p53; and EGFR; FACTOR-BINDING PROTEIN-5; TYROSINE KINASE-ACTIVITY; FALSE DISCOVERY RATE; PROGESTERONE-RECEPTOR; ESTROGEN-RECEPTOR; ENDOCRINE THERAPY; AKT ACTIVATION; GROWTH; EXPRESSION; GENE